PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 6 GIANYAR - Raraswari, Komang Ayu; Mariani, Ni Nyoman; Ayu Suciartini, Ni Nyoman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low Indonesian language learning outcomes of fifth-grade students at SD Negeri 6 Gianyar are due to the lack of use of engaging learning media, which leads to students being less active and easily bored during the learning process. One effort that can be made to improve student learning outcomes is through the use of comics in learning. This study aims to determine the effect of comics on the Indonesian language learning outcomes of fifth-grade students at SD Negeri 6 Gianyar. The experimental design used a nonequivalent control group design. The theory used in this study is the theory of learning media and learning outcomes. The study population was 98 fifth-grade students, with a sample of 50 students from class VA as the experimental class and 48 students from class VB as the control class. The data collection technique used an objective test in the form of multiple choices through a pretest and post-test. Data analysis was carried out using descriptive statistics and inferential statistics with the help of the SPSS program. The results showed that the average pretest score of the experimental class was 67.7 and the control class was 66.67. After being given treatment, the average post-test score of the experimental class increased to 86.92, while the control class became 77.52. The results of the hypothesis test using the independent sample t-test obtained a significance value of 0.000 <0.05 so that Ha was accepted and Ho was rejected. Thus, it can be concluded that the use of comic media has a significant effect on the Indonesian language learning outcomes of fifth grade students of SD Negeri 6 Gianyar.